Extracellular directed ag NPs formation and investigation of their antimicrobial and cytotoxic properties - Berrak Dumlupinar Altinsoy; Gokce Şeker Karatoprak; Ismail Ocsoy (Elsevier, 2019)
The use of microbial cell culture a valuable tool for the biosynthesis of nanoparticles is considered a green technology as it is eco-friendly, inexpensive and simple. Here, the synthesis of nanosilver particle (AgNP) from the yeast, Saccharomyces cerevisiae, gram (+), Bacillus subtilis and gram (−), Escherichia coli was shown. In this field we are the first to study their the antimicrobial effects of the microorganisms mentioned above against pathogens and anticancer activity on MCF-7 cell line. Silver nanoparticles in the size range of 126-323 nm were synthesized extracellularly by the microorganisms, which have different cell structures. Optical absorption, scanning electron microscopy, and zetasizer analysis confirmed the silver nanoparticles formation. Antimicrobial activity of AgNPs was evaluated the minimum inhibition concentration and disc diffusion methods. AgNPs inhibited nearly 90% the growth of Gram-positive Listeria monocytogenes, Streptococcus pneumoniae and Gram-negative Haemophilus influenzae, Klebsiella pneumoniae, Neisseria meningitidis bacterial pathogens. Anticancer potentials of AgNPs were investigated by MTT method. The synthesized AgNPs exhibited excellent high toxicity on MCF-7 cells and had a dose-dependent effect on cell viability. Especially AgNP 2 eliminated 67% of the MCF-7 cells at the concentration of 3.125 μg/mL. We found that extracellular synthesis of nanoparticles from microbial culture may be 'green' alternative to physical and chemical methods from the point of view of synthesis in large amounts and easy process. Keywords: Antimicrobial activity, Cytotoxicity, Extracellular synthesis, Silver nanoparticle